The implementation of continuing professional teacher development policy in the Western Cape : constraints and opportunities - Johns, Lynne Andrea (Cape Peninsula University of Technology, 2018)
Continuing Professional Teacher Development (CPTD) policy is an initiative intended to up-skill teachers, and in so doing improve schooling and learner achievement. CPTD involves the participation of teachers in various developmental activities for which they earn CPTD points. The professional development of teachers in South Africa has been erratic and, as a consequence, there has been a decline in the quality of teachers. Despite there being formal structures in place, policy implementation continues to be a problem. The purpose of this study was to identify constraints and opportunities regarding CPTD policy implementation in the Western Cape. The research tradition of interpretivism was chosen, allowing for a qualitative case study design to be employed. The non-probability sampling method was used to select a purposive sample of three WCED officials and four school principals. Convenience sampling was applied in identifying 24 teachers. Other data were drawn from policy documents. The study was conducted in an urban and rural district within the Western Cape. This study is significant in that it informs policy makers and implementers, and other stakeholders about the constraints and opportunities with regard to CPTD implementation and in so doing, paves the way for more effective implementation. Findings revealed that constraints outweighed opportunities. In spite of time constraints, principals and teachers reported that they are in support of professional development, but are not in support of the CPTD management system implemented by SACE. They do not agree with the one-size-fits-all approach to implementation, nor the focus of development being the collection of CPTD points. It is thus deemed that a review of the CPTD policy is necessary in order to clear the misconception that accumulation of PD points is the primary focus of CPTD. Granted, teachers would still need to collect points to monitor their growth. A recommendation is made in this study to improve the system and ensure that it is functional and accessible to all teachers at all times, including those in rural districts.
Thesis (MEd)--Cape Peninsula University of Technology, 2018.
Keywords: Teachers -- Training of; Teacher effectiveness; Effective teaching; Academic achievement